2021
DOI: 10.1038/s41598-021-87559-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and brain mechanisms mediating conditioned flight behavior in rats

Abstract: Environmental contexts can inform animals of potential threats, though it is currently unknown how context biases the selection of defensive behavior. Here we investigated context-dependent flight responses with a Pavlovian serial-compound stimulus (SCS) paradigm that evokes freeze-to-flight transitions. Similar to previous work in mice, we show that male and female rats display context-dependent flight-like behavior in the SCS paradigm. Flight behavior was dependent on contextual fear insofar as it was only e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
31
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 76 publications
9
31
2
1
Order By: Relevance
“…While our 75 dB noise stimulus is less intense than the 98-120 dB noise used in typical acoustic startle studies, we are observing an unconditional noise elicited response that also decreases with habituation (Experiment 4). Furthermore, our data and those of Totty et al (2021) indicate that these responses require a fearful context in order to occur. Fear is well known to potentiate startle responses (Brown, et al, 1951;Davis, 1989).…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…While our 75 dB noise stimulus is less intense than the 98-120 dB noise used in typical acoustic startle studies, we are observing an unconditional noise elicited response that also decreases with habituation (Experiment 4). Furthermore, our data and those of Totty et al (2021) indicate that these responses require a fearful context in order to occur. Fear is well known to potentiate startle responses (Brown, et al, 1951;Davis, 1989).…”
Section: Discussionsupporting
confidence: 65%
“…Thus, the difference between the paired and unpaired groups reported by Totty et al (2021) Initial reports suggest a sex difference in this noise-elicited flight behavior such that female rats show more of this behavior than males (Gruene et al, 2015). Within each experiment, we found no such sex differences between male and female mice for the PAR and darting measures of flight behavior, and Totty et al (2021) similarly found no sex differences in such behavior in male and female rats. To further increase the power of such an analysis for sex differences, we pooled all of the groups across the four experiments which received noise-shock pairings.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations